Energy efficiency maximization in MIMO links aided by metasurfaces with global reflection constraints - Ayşegül Ilay Tunalı; Robert Kuku Fotock; Alessio Zappone; Giorgio Taricco; Giuseppa Alfano; Hakan Ali Çırpan (EURASIP Journal on Advances in Signal Processing)
Abstract This work develops two radio resource allocation algorithms to optimize the energy efficiency of a multiple-input multiple-output (MIMO) communication system where a metasurface is deployed near the transmit antenna array to create a reconfigurable holographic beamforming structure. The design involves jointly optimizing the transmit covariance matrix and the reflection coefficients of the reconfigurable holographic surface (RHS). Two methods are proposed for this joint optimization. In both approaches, the RHS matrix is optimized using sequential fractional programming. However, the transmit covariance matrix is optimized differently: the first method employs fractional programming, while the second method utilizes a search within a standard-compliant codebook. The two algorithms are compared, showing that the codebook-based method achieves performance with only a limited gap compared to the more complex sequential fractional programming algorithm. The analysis considers both a nearly-passive RHS and an active one equipped with analog amplifiers.